Emerging Roles of Bromodomain Protein 4 in Regulation of Stem Cell Identity. (25th September 2021) - Dey, Anusree; Uppal, Sheetal; Giri, Jayeeta; Misra, Hari Sharan
Abstract: Understanding the mechanism of fate decision and lineage commitment is the key step for developing novel stem cell applications in therapeutics. This process is coordinately regulated through systematic epigenetic reprogramming and concomitant changes in the transcriptional landscape of the stem cells. One of the bromo- and extra-terminal domain (BET) family member proteins, bromodomain protein 4 (BRD4), performs the role of epigenetic reader and modulates gene expression by recruiting other transcription factors and directly regulating RNA polymerase II elongation. Controlled gene regulation is the critical step in maintenance of stem cell potency and dysregulation may lead to tumor formation. As a key transcriptional factor and epigenetic regulator, BRD4 contributes to stem cell maintenance in several ways. Being a druggable target, BRD4 is an attractive candidate for exploiting its potential in stem cell therapeutics. Therefore, it is crucial to elucidate how BRD4, through its interplay with pluripotency transcriptional regulators, control lineage commitment in stem cells. Here, we systemically review the role of BRD4 in complex gene regulatory network during three specific states of stem cell transitions: cell differentiation, cell reprogramming and transdifferentiation. A thorough understanding of BRD4 mediated epigenetic regulation in the maintenance of stem cell potency will be helpful to strategically control stem cell fates in regenerative medicine. : Bromodomain protein 4 (BRD4) mediated transcription elongation in complex gene regulatory network during different stages of stem cell transitions. BRD4 modulates gene expression by recruiting PTEF-b for successful RNA polymerase II pause release and transcriptional elongation. Treatment with BET inhibitors blocks the transcriptional elongation and expression of pluripotency genes.